Pengaruh Kepuasan Kerja Terhadap Kinerja Dosen Program Studi Perhotelan Pendidikan Tinggi Swasta Kota Bandung - Erie Hidayat Sukriadi (Tourism Scientific Journal, 2021)
This research’s title is "The Influence of  Work Satisfaction on the Lecturer Performance Full Time Lecturer Hospitality Study Program in Private Universities in Bandung", The purpose of this research are to know the condition of job satisfaction and full time lecturer performance Hospitality Study Program in Private Universities in Bandung, and also to analyze the influence of lecturer job satisfaction on the lecturer performance in the Private Universities Hospitality Study Program In Bandung. The method used in this research is survey method with the level of explanation is associative. The Respondents in this research is using census with total of respondents are 57 respondents. The Data collection techniques are using literature study and questionnaires. The results of this research (1). job satisfaction and lecturer performance in high category. (2). The influence of the lecturer job satisfaction on the lecturer performance is at 63,50%, so it can be concluded that the job satisfaction variable has a positive and significant effect on the lecturer performance variable.